3D Printing Cementitious Materials Containing Nano-CaCO3: Workability, Strength, and Microstructure - Yang, Huashan; Li, Weiwei; Che, Yujun (Frontiers in Materials, 2020)
The technology of 3D printing concrete has undergone rapid development in the last few years due to its lower environmental impact than that of conventional concrete. To investigate the fresh and hardened behaviour as well as the microstructure of 3D printing cementitious materials (3DPC) containing nano-CaCO3 (NC), four replacement ratios of NC to binder from 1% to 4% are investigated. 3DPC without NC is as a control specimen. The workability, such as fluidity, extrudability, printability limit, and deformation under self-weight, flexural and compressive strength of 3DPC, are tested. The strength development of 3DPC is compared with that of the cast specimens. The hydration products and microstructure of specimens were also investigated by derivative thermogravimetry (DTG), thermogravimetry analysis (TGA), scanning electron microscope (SEM) and backscattered electron imaging (BSE). Results indicate that the fluidity, extrudability, printability limit, and deformation under self-weight demonstrate a decreasing tendency to increase NC’s content. This is attributed to the large specific surface area of NC, which increases the mixtures’ consistency. Adding 2% of NC exhibited about 7.2%, 39.1%, and 22.5% higher compressive strength than that of the control mixture at 7, 28, and 90 days. The enhancement of strength of 3DPC with NC can be ascribed to the filler effects and seeding effects of NC. Furthermore, NC refines the pore structure and improves the microstructure of 3DPC due to its filler effects and accelerating effects.